THE COMPOSITION CATCHS OF BOTTOM GILLNET IN SUNGAI RAYA WATERS, MERAL DISTRICT, KARIMUN REGENCY, RIAU ISLANDS PROVINCE - Saputra, Rio; Yani, Alit Hindri; Brown, Arthur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research was conducted in April 2019 in Sungai Raya waters, Meral District, Karimun Regency Riau Island Province. The purpose of this research is to find out the types and the number of target fish catches and bycatch on the bottom gillnet. The method used is a survey method which is then analyzed descriptively and using a shortening calculation.The catch during the study was 390,4 kg or 93 tails. The total catch of the bottom gillnet during the study that the target fish, namely the kurau fish, were obtained as the main catch based on the weight of 79,8% and the remainder as a bycatch of 20,2%. While based on the individual obtained as the main catch of 60,2% and remainder as a bycatch of 39,8%. In this study the shortening value of the fishing gear operated was 40%, then the fish is caught gilled. During the study the temperature ranges between 30-310C, the current velocity ranged from 1,3-1,7 mil/jam, and water depths range between 9,1-36 meter.Keywords: Bottom Gillnet, Composition Catch Fish, Sungai Raya Waters